Rethinking the Rentier Curse - Adeel Malik (Revue Internationale de Politique de Développement)
The Middle Eastern political economy has long been studied through the prism of the resource curse—that is, how resource riches undermine the region’s economic and political development. While many of the region’s pathologies are rooted in an economic structure heavily reliant on external windfalls, the existing literature tends to overstate the role of oil. This research note develops the case for a broader conceptualisation of rents that includes not just windfalls from hydrocarbons, but also rents derived from aid, remittances and government manipulation of the economy. Reliance on these rent streams is the ‘original sin’ that perpetuates underdevelopment. Discussions of Arab political economy should therefore be framed as part of a broader enquiry into the relationship between rents and development. This requires, in turn, a deeper understanding of business–state relationships and the role of regional linkages in development.